Patient characteristics as predictors of recurrence of atrial fibrillation following cryoballoon ablation. Issue 6 (9th April 2019) - Bavishi, Aakash A.; Kaplan, Rachel M.; Peigh, Graham; Diaz, Celso L.; Baman, Jayson R.; Trivedi, Amar; Wasserlauf, Jeremiah; Shen, Mark J.; Sattayaprasert, Prasongchai; Chicos, Alexandru B.; Kim, Susan; Verma, Nishant; et al.
Abstract: Background: While several studies have evaluated predictors for atrial fibrillation (AF) recurrence following catheter ablation, there are limited data specific to cryoballoon ablation (CBA). Methods: We analyzed a prospective registry of patients at a single institution who underwent CBA. Recurrence of AF (RAF) was defined as recurrence of AF by 12‐month follow‐up, excluding the 3‐month blanking period. Univariate analysis was performed to evaluate predictors of RAF. Receiver operating characteristic analysis was used to compare and evaluate the performance of various risk scores for discriminating risk of RAF. Results: There were 542 patients included in the analysis with mean age 61.3 ± 10.6 years, 67.9% male, and 51.6% paroxysmal AF (PAF). Overall, only left atrial diameter (LAD) > 40 mm and ERAF (early recurrence of AF within 0‐3 month blanking period) were significant predictors of RAF. In the PAF specific subgroup, LAD > 40 mm, AF duration > 12 months, prior stroke or transient ischemic attack, ERAF, and having previously failed an antiarrhythmic drug were significant predictors of RAF. In persistent AF (PeAF) subgroup, obstructive sleep apnea (OSA) and ERAF were significant predictors of RAF. Out of clinical risk scores tested, BASEAF2 had the highest performance with area under the curve of 0.646 (95% confidence interval [0.548, 0.708]; P < .01). Conclusions: In this single‐center retrospective study of CBA, we found only LAD > 40 mm and ERAF to be predictors of RAF. We identified OSA as a potential targetable risk factor in PeAF patients undergoing CBA. Out of risk scores tested for discriminating risk of RAF, BASEAF2 had the best performance.